MORPHOGENESIS OF LUNG DAMAGE AT THE INFECTION OF EXPERIMENTAL ANIMALS BY ASSOCIATION OF CULTIVATED AND NONCULTURED FORMS OF BACTERIA P. AERUGINOSA AND S. AUREUS - Сахаров, Сергей Павлович; Фролова, Ольга Сергеевна; Молокова, Ольга Александровна (Medicine in Kuzbass, 2021)
Objective – currently, associated infections in the structure of human infectious diseases cause high mortality, difficulty in diagnosis and treatment. In the literature, the issue of lung pathomorphology during infection with P. aeruginosa and S. aureus in cultivated and uncultivated forms of bacteria is insufficiently illuminated. The aim of this study is to study the morphological features of lung damage in experimental infection caused by the association of cultivated and uncultivated forms of P. aeruginosa and S. aureus bacteria. Methods. The experiment was carried out on 58 rabbits of the «Soviet Chinchilla» breed, divided into 3 experimental groups. To infect rabbits, a suspension of cultivated and uncultivated forms of bacteria P. aeruginosa and S. aureus isolated from patients undergoing treatment in the burn department of the Regional Clinical Hospital № 1 of the city of Tyumen was used. A microscopic examination of the lungs was performed using standard histological techniques. Results. In the first group of experimental animals, the lethality was 22 (84.6 %) rabbits, of which on the 8-9 day – 18 (81.8 %) and on the 12th day – 4 animals (18.2 %). In group II, 24 (92.3 %) rabbits died, from the 2-5th day – 18 (75 %) and on the 8th day of the experiment – 6 (25 %) animals. Morphological changes in the lungs correspond to the first phase of diffuse alveolar injury (DAP) - exudative changes. With the use of cultured forms of bacteria, lethality is lower, morphological changes in the lungs correspond to the late manifestation of the DAP exudation phase (atelectasis, parenchymal distelectasis, hemorrhages and inflammatory lymphocytic infiltration of the interstitium). When uncultivated forms of P. aeruginosa and S. aureus bacteria are used, lethality is higher due to early changes in the phase of DAP exudation (alveolar edema, necrosis and desquamation of endothelial cells and type I alveocytes). Conclusions. In animals that survived this critical line (days 2-5), the process acquires a favorable course due to the transition from uncultivated to cultivated forms of bacteria, the morphological picture of lung damage corresponds to the late manifestation of the DAP exudation phase.